The Impact of Refugee Crisis on Children’s Welfare in Nakivale Refugee Camp in Bukanga County About 50KM South of Mbarara in Isingiro District - Ritah Turyagyenda (Uganda Christian University, 2024)
This study highlighted the the impact of refugee crisis on the welfare of refugee children in Nakivale Refuge Camp in Isingiro District. This research is guided by objectives which included: To find out the causes of refugee crisis that has impacted negatively on the lives of children in Isingiro District, analyzing the strategies that have been put into place to reduce the impacts of conflict on children in Isingiro District and to find out the negative contribution of refugee crisis on children welfare. The study utilized a cross-sectional methodology, collecting data from a sample population at a single point in time where qualitative and quantitative method of data collection was used. The data was collected using interviews and questionnaires as a method of data collection, employing purposive sampling, and qualitative looking into the effects of the refugee crisis on children's welfare in the target group of over 40,000 young people. A sample size of 383 respondents who were male and female. The findings showed that a number of methods have been created to address the impact of the crisis on children's well-being, some of which are described in this research. It is critical to understand that in order to provide a safe environment for refugee children, persistent investment and cooperation across different sectors are required.
Undergraduate research